2006
DOI: 10.3892/or.16.4.677
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the severity of liver disease and fibrotic change: The usefulness of hepatic CT perfusion imaging

Abstract: This study assessed the utility of CT perfusion for quantitative assessment of liver function and fibrosis. Tissue blood flow (TBF), tissue blood volume (TBV), mean transit time (MTT) and hepatic arterial fraction (HAF) were measured with CT perfusion using the deconvolution algorithm in 38 patients with chronic liver diseases and 10 patients without liver disease. Using Child-Pugh classification, 21 patients were classified as Child A, 10 as Child B, and 7 as Child C. In 20 patients, the degree of fibrosis wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 34 publications
4
60
1
Order By: Relevance
“…In cirrhotic liver parenchyma, the arterial enhancement fraction determined by quantitative mapping is increased with increasing severity of cirrhosis (9,14). In a recent report, Kang et al (9) demonstrated that the use of quantitative mapping of the arterial enhancement fraction improved the diagnostic performance of multiphasic CT in detection of cirrhosis and prediction of disease severity.…”
Section: Perfusion Imaging In Cirrhosismentioning
confidence: 99%
“…In cirrhotic liver parenchyma, the arterial enhancement fraction determined by quantitative mapping is increased with increasing severity of cirrhosis (9,14). In a recent report, Kang et al (9) demonstrated that the use of quantitative mapping of the arterial enhancement fraction improved the diagnostic performance of multiphasic CT in detection of cirrhosis and prediction of disease severity.…”
Section: Perfusion Imaging In Cirrhosismentioning
confidence: 99%
“…This tube voltage and/or scanner-dependent phenomenon for CT numbers could be largely avoided with iodine concentration measurement, which makes accurate quantification possible. The value of AIF in patients with normal liver functionality in the control group was 0.25, which was in the range of normal HPI values reported [5,17]. It indicated that perhaps there was a good correlation between AIF and HPI.…”
Section: Discussionmentioning
confidence: 69%
“…The HPI, which is the ratio of hepatic arterial perfusion to that of total perfusion, is one of the most commonly obtained hepatic CT perfusion parameters [17]. The normal value of HPI varies according to different reports [5,18], which perhaps is a result of the different mathematic models, scanners or patient selections involved. However, in general, the normal value of HPI is between 1/4 and 1/3.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations